Muslim and non-Muslim fund managers' perception of environmental information - Mohd Said, Ridzwana; Sulaiman, Maliah; Nik Ahmad, Nik Nazli (Universiti Putra Malaysia Press, 2014)
The Islamic concept of accountability includes full disclosure of information to wider stakeholders, be it information on companies' financial or non-financial matters. The objective of this study was to examine the differences in perception between Muslim and non-Muslim fund managers regarding the usefulness of information on the environment in investment decision making. A questionnaire survey was used and 59 responses were received. No differences were found in perception between Muslim and non-Muslim fund managers related to several companies' environmental attributes and environmental information types. This implies that the Islamic worldview is not reflected in the perception of Muslim fund managers. This study makes a significant contribution to research in environmental reporting, particularly for companies and practitioners in Malaysia in the context of accountability in Islam. The study suggests some preliminary insights into the use of environmental information by Muslim and non-Muslim fund managers in Malaysia.